Towards a model for measuring holistic performance of professional Football clubs. (2nd January 2017) - Plumley, Daniel; Wilson, Rob; Ramchandani, Girish
Abstract : This paper introduces an experimental model to measure the holistic performance of professional football clubs. The model utilizes a selection of established financial and sporting indicators, which are weighted in accordance with their perceived relative importance and in relation to components of financial management and governing body regulations. The paper uses data pertaining to clubs competing in the English Premier League to demonstrate the outputs of the model. The authors argue that although the model is experimental, it still provides a useful platform to analyse performance of football clubs through further scientific investigation.